Magnetic Resonance Spectroscopic Imaging of Tumor Metabolic Markers for Cancer Diagnosis, Metabolic Phenotyping, and Characterization of Tumor Microenvironment. Issue 2 (12th June 2013) - He, Qiuhong; Xu, Ray Z.; Shkarin, Pavel; Pizzorno, Giuseppe; Lee-French, Carol H.; Rothman, Douglas L.; Shungu, Dikoma C.; Shim, Hyunsuk
Abstract : Cancer cells display heterogeneous genetic characteristics, depending on the tumor dynamic microenvironment. Abnormal tumor vasculature and poor tissue oxygenation generate a fraction of hypoxic tumor cells that have selective advantages in metastasis and invasion and often resist chemo- and radiation therapies. The genetic alterations acquired by tumors modify their biochemical pathways, which results in abnormal tumor metabolism. An elevation in glycolysis known as the "Warburg effect" and changes in lipid synthesis and oxidation occur. Magnetic resonance spectroscopy (MRS) has been used to study tumor metabolism in preclinical animal models and in clinical research on human breast, brain, and prostate cancers. This technique can identify specific genetic and metabolic changes that occur in malignant tumors. Therefore, the metabolic markers, detectable by MRS, not only provide information on biochemical changes but also define different metabolic tumor phenotypes. When combined with the contrast-enhanced Magnetic Resonance Imaging (MRI), which has a high sensitivity for cancer diagnosis, in vivo magnetic resonance spectroscopic imaging (MRSI) improves the diagnostic specificity of malignant human cancers and is becoming an important clinical tool for cancer management and care. This article reviews the MRSI techniques as molecular imaging methods to detect and quantify metabolic changes in various tumor tissue types, especially in extracranial tumor tissues that contain high concentrations of fat. MRI/MRSI methods have been used to characterize tumor microenvironments in terms of blood volume and vessel permeability. Measurements of tissue oxygenation and glycolytic rates by MRS also are described to illustrate the capability of the MR technology in probing molecular information non-invasively in tumor tissues and its important potential for studying molecular mechanisms of human cancers in physiological conditions.